Aspek Religi Pada Masa Pemerintahan Raja Ugrasena (Kajian Epigrafi) - Wicakshana Essa Putra, Made; Tara Wiguna, I Gst Ngr; Sapta Jaya, Ida Bagus (Humanis, 2018)
Religion is an important part of human life, because it is considered to have meaning in life. Because it takes an important role in the existence of society and social community. All aspect of religion contained in the inscription have an important role in the reign of the king Ugrasena. The problem discussed in this research was what are the aspects of religion that contained in the inscription during the reign of the king Ugrasena and related to the religious impact to the social life of society during the reign of the King Ugrasena This research used some method of collecting data, analyzing the data, and theory to solve the problem. The method of collecting data that used were observation, literature review, and interview. The next step, the data were procesed by using qualitative analysis, contextual analysis and analysis etnoarchaeology. The theories that used as the basic theory in this research is the theory of religion, ritual theory and fungsional structural theory to determine the role of religion to social life of the society during the reign of King Ugrasena. The results of this study found that the religious aspects, which were  contained in inscriptions during the reign of King Ugrasena that there were the begining of the sects in ancient Bali, religious ceremony, sacred building, the tools of religious ceremony, as well as the religious figures in the erly days of ancient Bali. The role of religion to the social life of the society in the reign of the King Ugrasena showed that religion had a role in the society social interaction such as the basis of reference in the society, and also play a role as the legitimation of the power of King Ugrasena Kingdom